The relationship between aerobic capacity and match performance in team-handball - Tunc Gülsen, T.; Koc, H.; Özen, G. (Kinesiologia Slovenica, 2017)
The aim of this research was to determine the relationship between aerobic capacity and match performance of elite handball players. A total of 12 male handball players who competed in the male super league had participated in the study as volunteers. The participants` mean age was 25.25±2.76 years, height was 188.3±4.8 cm and weight was 90.00±6.22. All participants had a training experience over 7 years. For measuring aerobic capacity, the Cooper 12-minute run-walk test was performed. To determine the match performance of players, "Performance Appraisal Inventory in Handball" developed by Ulrich was used. Study results show that there was a relationship between aerobic capacity and match performance of participating handball players. Our findings indicated that athletes with high positive score have higher match performance and aerobic capacity. As a result, aerobic capacity may use as a predictor of the match performance in team-handball.